Pre-anesthesia Clinic Guideline for One Day Surgery and Minimally Invasive Surgery by the Royal College of Anesthesiologists of Thailand - Wongyingsinn, Mingkwan (Thai Journal of Anesthesiology, 2021)
In the present, pre-anesthesia clinics (PAC) play an important role in assessing and preparing patients and their relatives prior to surgery. The Royal College of Anesthesiologists of Thailand (RCAT) established this guideline aimed to guide the establishment and provision of clinical evaluation and preparation before one day surgery and minimally invasive surgery. The objective is to reduce the incidence of cancellation or postponement of the surgeries due to patients’ factors, reduce hospitalized duration and urgent medical consultation prior to surgery, and increase patients and relatives’ satisfaction.